PROMOTING A WEBSITE WITH THE HELP OF SEO USING PPC (PAY PER CLICK) - Shrivastva, Rajneesh; Gautam, Chandra Shekhar; Kar, Sajal Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nowadays, the promotion of a website plays an important role in any organization or business. There are many ways to promote anywebsite and PPC is one of them. It is an advertising model where searchers are directed to the advertiser’s page through paid listings. Every time a user clicks on a paid listing, the advertiser pays a onetime fee. Nowadays, everyone has their own website and we do not have time to manage or promote the website, so PPC is one of the best ways to solve this problem. This article explains how you can keep the website in the top position with the help of PPC by paying only what is necessary.